Architecture Building Redesign as an Effort to Optimize Studio Activities at the Department of Architecture, Faculty of Engineering, Brawijaya University - Ramadhani, Nurul Fauziyah (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
Studio space is a vital space in higher education buildings, especially in the Architecture Study Program because the process of creativity and in-depth learning of advanced theory is carried out in this space to support the architectural professional education program, namely 4 + 1 years set by the Indonesian Architect Association (IAI). The design of the studio space of the Department of Architecture Building, Faculty of Engineering (FT), Universitas Brawijaya (UB) cannot accommodate all equipment and furniture to support lecture activities based on the description of the National Education Standards Agency (BSNP) that the studio space requirements are 4 m2 / student according to the capacity of the room or a minimum of 45 m2 which can accommodate equipment that can support the achievement of professional competencies set by the Indonesian Institute of Architects (IAI). Another problem is the limited land and considerations regarding the height of the building that does not exceed the FT UB Dean's Building. In finding related data, the approach used is empiricism based on experience and observation that must be felt and done by the observer himself. In the Redesign results, the R. Studio circulation used is 30% adjusting the standard demands of user physical comfort by making mezzanines on the three floors of the S1 Studio Room so that the height of the inter-floor space becomes 5-6 meters with the aim of supporting 3 studios for 3 classes for 24 hours in one (1) semester of lectures. Keywords: Studio Space, Empiricism, Circulation, Land Limitations